Some Word Formation Processes in Zamyad-Yasht of Avesta - Sedighi, Shima; Najari, Hossein (LANGUAGE ART, 2023)
The speakers of every language avail themselves of word formation processes and analogy to create new words as to be able to express what they intend. What is meant by a word is the mental picture which is shared by all. The present study aimed at examining some word formation processes involved in making adjectives in Zamyad-Yasht. Zamyad-Yasht, the 19th Yasht in Avesta, comprises 96 parts/sections and is about Farr-e Kyani. The results of the study showed that of the word formation processes, including derivation, compounding, derivation and compounding, clipping, conversion, and reduplication, discussed in this study, derivation and compounding were most frequently observed, respectively.